50 ans d’histoire du projet JARI : d’un grand projet contesté à un modèle d’éthique entrepreneuriale ? - Anna Greissing (L'Espace Politique)
Situated at the borders of the Brazilian Amazon, the Jari river region has been until the 1960ies almost exclusively populated by small communities scattered in the forest and living on the extraction of natural resources (rubber, Brazil nut). The arrival, in 1967, of the American businessman D.K. Ludwig, who had been invited by the Geisel military government to « valorize » a part of land in the Brazilian Amazon, provokes an important regional turnover: in the middle of an intact rain forest, the American businessman sets up an enormous economic development project, based on several large-scale agro-industrial (rice, cattle) and mining (kaolin) activities centered around the production of cellulose from monoculture plantation. Socially controversial and economically unprofitable, this project, who gained fame under the name of " the Jari project ", has nevertheless subsisted until our days and claims more than 1,2 millions of hectares in the Jari river region. However, the XXI century project has essentially evolved from a strongly criticized enterprise that « inexorably devoured human and natural resources » to a modern, highly technologized business that includes several companies and activities certified by the FSC (paper, cellulose, and tropical wood extraction). Moreover, the new management team at the head of the project since 2000 (the Orsa group, a holding with domicile in São Paulo), stands out in the Amazon context as an innovative business model, based on the principles of sustainable development and inspired by the idea of corporate social responsibility (CSR). As such, the new Orsa management has indeed succeeded to make a profitable enterprise out of the indebted Jari project, and has engaged in transforming the company’s social and environmental liabilities into economic assets. In order to mitigate the contradictions of economic development provoked by the clash of two contrasting socioeconomic models – agro-business and traditional forms of agriculture and forest resource extraction- the Orsa group has created a company-intern Foundation that aims at the conception and implementation of social and economic development projects with and for the benefit of the local populations. This article discusses the potential but also the limits of CSR as a key strategy for the new company’s management of its huge territory in the Amazon, in the context of the region’s and the project’s historical evolution.